The Torreón of Machu Picchu: an astronomical observatory? - Kościuk, Jacek; Ziółkowski, Mariusz (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
The Torreón is one of the most emblematic buildings of Machu Picchu. Since 1929, different archaeoastronomical studies have been carried out on this building to verify its function as an astronomical observatory. The authors of the present text analyse in detail these hypotheses using a thorough survey of the structure created from 3D scans and digitised models. The analysis concludes that we can take as established evidence that the builders of the tower designed it according to some solar orientations, but without the purpose of erecting an astronomical observatory as was apparent in the cases of Intimachay and Inkaraqay.